Premedication Use Before Infliximab Administration: A Cross-sectional Analysis. Issue 1 (9th December 2016) - Picoraro, Joseph; Winberry, Gabriel; Siegel, Corey A.; El-Matary, Wael; Moses, Jonathan; Grossman, Andrew; Park, K.T.
Abstract : Article first published online 9 December 2016. Abstract : Background: Premedications are commonly given to patients with inflammatory bowel disease before intravenous infliximab administration. We aimed to (1) describe practice variability; and (2) determine clinician rationale for premedicating patients with inflammatory bowel disease before infliximab administration. Methods: We developed a cross-sectional electronic survey after comprehensive literature review to assess practice variability and clinician rationale for premedication use before infliximab. An optional postsurvey quiz assessed clinicians' understanding of the available literature. The survey was distributed through members-only NASPGHAN and Crohn's and Colitis Foundation of America (CCFA) listservs and American Gastroenterological Association (AGA) and American College of Gastroenterology (ACG) web-based discussion boards. Results: Three hundred seventy-nine unique respondents with a 93.3% survey completion rate comprised 331 (87%) and 45 (12%) pediatric and adult gastroenterologists. Among numerous options for premedications, acetaminophen (66%) and diphenhydramine (64%) were most often given before each infliximab infusion. Only 20% did not routinely use premedications. There was heterogeneity of premedication use between gastroenterologists within the same clinical practice. Of 328 (87%) respondents who completed the knowledge assessment quiz, only 18% identified the association of diphenhydramine use with increased reaction. Conclusions: There is high interpractice and intrapractice variability for premedication use before infliximab administration. Clinician rationale for premedicating patients seems to be driven by individual preference or group practice habit. Improved knowledge of the evidence may assist in decreasing overuse of premedications, particularly diphenhydramine.